O teatro das heroínas de Tejucupapo: patrimônio vivo do estado de Pernambuco. - Melo, Rizangela Pereira de (2024)
The Heroines of Tejucupapo were the protagonists in the battle that took place on April 24, 1646. It is said that they prevented their village from being looted by the Dutch, who invaded Tejucupapo, an area in the northern forest of Pernambuco, at a moment of fragility, since the men would be away selling their products in the city. With the village with less people, the duch executed what would be the third invasion aiming looting the food and resources from the residents. Four women organized the defense of the village, emerging victorious by expelling the invaders. They were: Maria Camarão, Maria Clara, Maria Quitéria and Maria Joaquina. The defense was planned and elaborated with what they had at hand: sticks, sickles, household itens and boiled water with pepper. This victorious battle, with the participation of women, it is part of the history of the Tejucupapo Community and it´s inspiring until the presente day. The´´Heroine’s Battle´´ has been staged in the community for 30 years. The Theatre of Heroines it’s made through the determination and perseverance of its founder, Luzia Maria da Silva. Finally, in the year of 2022, the Theatre, as a collective, achieved public acknowledgement by being certified as a living heritage of the state of Pernambuco, a lifetime title, which guarantees them, in addition to a financial grant, the continuity and perpetuation of the knowledge for the future generations. This study had as theoretical basis the reflections of François Hartog, Maurice Halbwachs and Roger Chartier and for the methodological analysis of the images, were used the perspectives of Ana Maria Mauad. At lenght, as a final productthe ressearch is committed to creating an official website for the Tejucupapo’s Heroines theatre pursuing providing it something valuable and useful with aiming contributing to it’s dissemination.